2018
DOI: 10.3390/healthcare6010015
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Investigate the Effectiveness of the Prevention of Aspiration Pneumonia Using Recommendations for Swallowing Care Guided by Ultrasound Examination

Abstract: Prevention for aspiration pneumonia requires assessment of aspiration and adequate swallowing care. This randomized controlled trial aimed to investigate the effectiveness of ultrasound examination and recommendations for swallowing care for the reduction of aspiration and pharyngeal post-swallow residue as compared with standard swallowing care. Twenty-three participants were randomized to the intervention group and 23 to the control group. The intervention consisted of four ultrasound examinations during mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In the specific RCT, the intervention group that introduced the cough reflex test did not show any significant difference in the incidence rate of pneumonia compared to the control group. This result is in agreement with the findings from another RCT that evaluated the effectiveness of ultrasound examinations (Miura et al, 2018). In the RCT, the odds ratios of the frequency of aspiration, the frequency of pharyngeal residue, and the incidence of aspiration pneumonia were 0.30 (95% CI: 0.03–3.15), 0.63 (95% CI: 0.10–4.21), and 2.09 (95% CI: 0.18–24.87), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the specific RCT, the intervention group that introduced the cough reflex test did not show any significant difference in the incidence rate of pneumonia compared to the control group. This result is in agreement with the findings from another RCT that evaluated the effectiveness of ultrasound examinations (Miura et al, 2018). In the RCT, the odds ratios of the frequency of aspiration, the frequency of pharyngeal residue, and the incidence of aspiration pneumonia were 0.30 (95% CI: 0.03–3.15), 0.63 (95% CI: 0.10–4.21), and 2.09 (95% CI: 0.18–24.87), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…If clinical professionals suspect individual aspiration or pharyngeal residue from their symptoms, such as coughing, wet voice, and delayed swallowing, they can perform ultrasound examination to visualize the aspirated bolus and pharyngeal residue. Moreover, a randomized controlled trial (RCT) that applied recommendation of swallowing care based on ultrasound examinations during mealtimes showed a trend of reducing the frequency of aspiration and residue in the intervention group (Miura et al, 2018). This clearly suggests that ultrasound assessments can serve to detect aspiration and pharyngeal residue and contribute to the prevention of aspiration pneumonia; however, this method requires skill to obtain and to evaluate the images.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of detecting pharyngeal residue in the epiglottic vallecula was 86.7%, and the specificity was 63.6% . Moreover, swallowing care guided by frequent ultrasound examinations during mealtimes had a trend of reducing the frequency of aspiration and residue in a randomized controlled trial . Therefore, ultrasonography should be used to assess swallowing function in clinical practice.…”
Section: Comparison Of Swallowing Evaluation Methodsmentioning
confidence: 99%
“…Although ultrasound observation is not a diagnostic measure, it is useful to screen out risk of aspiration and residue and to guide swallowing care for preventing these outcomes. Our previous study [13] demonstrated the efficacy of recommendations for swallowing care utilizing the guide by ultrasound observation. Nevertheless, this study has some shortcomings.…”
Section: Introductionmentioning
confidence: 98%
“…Also, patients often refuse to receive VFSS because of pain and discomfort due to the insertion of an endoscope in the patient's nose. Therefore, nurses have some difficulties providing swallowing care because correct information is lacking about the patient's swallowing function more than 1 month until physicians perform VESS or VFSS [13].…”
Section: Introductionmentioning
confidence: 99%